Placental beginnings: Reconfiguring placental development and pregnancy loss in feminist theory. (August 2019) - DiCaglio, Sara
The placenta has played an important role in feminist theories of subjectivity; however, the placenta of feminist theory has been the fully functional placenta of what is considered a successful full-term pregnancy. Pregnancy loss, a topic that has been generally overlooked within feminist scholarship, is absent from feminist theories of the placenta. This article uses early placental development, particularly development that takes place before the placenta becomes fully functional as an organ for hormone production and interchange, as a space through which to consider theorising subjectivity, reproduction and relation through pregnancy loss. In so doing, I argue that turning our attention to the placenta's early development, regardless of outcomes, allows us to reimagine the role of process for feminist theories of subjectivity while also making room for a wider array of pregnancy outcomes, reinvigorating our ability to think about relations and models of hospitality that do not end as we might imagine.